When Authority Fails: Cognitive Dissonance, Storytelling, and Collective Sense-Making in Unanswered Prayers - Schüler, Sebastian (Research in the social scientific study of religion, 2022)
Authority is a social attribution that raises collective expectations. These attributions also define the roles between which authority is negotiated. In Evangelicalism, authority is attributed to God above all, and especially petitionary prayer raises high expectations towards God. However, these expectations may be disappointed and thus the authority relationship may be challenged, leading to attempts to restore the authority relationship at the individual and collective levels. In the sociology of religion, the role of authority holders has too often been emphasized. This paper, therefore, focuses on the role of submitting subjects and asks about reactions when authority fails. To this end, the theory of cognitive dissonance by Leon Festinger et al. is critically discussed and extended by means of a narrative sociology perspective. This new reading of Festinger et al. is then applied to the example of unanswered prayers in the 24-7Prayer movement.